Kemampuan Literasi Sains Peserta Didik Pada Mata Pelajaran IPA di Kelas V SDN 019 Koto Baru - Putri Gayo Mahbengi; Dea Mustika (CV. Rayyan Dwi Bharata, 2025)
This study aims to describe the scientific literacy skills of fifth-grade students in science subjects at SDN 019 Koto Baru. A quantitative descriptive survey method was applied, with a total sample of 27 students (15 male, 12 female). Quantitative data were obtained through a 20-item multiple-choice test measuring conceptual understanding, application of science knowledge in daily life, and critical thinking skills. Qualitative data were collected via semi-structured interviews with teachers and students. The instrument’s validity was tested using Pearson Product Moment correlation, and reliability using Cronbach’s Alpha (0.925). Item difficulty and discrimination indices were also analyzed. The results show that 74% of students scored ≥70 (high to very high categories), while 26% scored below 70. Students demonstrated emerging abilities in identifying scientific issues, explaining phenomena, and using scientific evidence, though competency levels varied. It is recommended that science learning be more contextual, problem-based, and involve direct observation to enhance scientific literacy evenly across students.